Palladium-catalyzed addition reaction of thioesters to norbornenes. Issue 37 (16th September 2015) - Arisawa, Mieko; Tanii, Saori; Yamada, Tomoki; Yamaguchi, Masahiko
Abstract: A palladium complex derived from Pd2 (dba)3 and tris(2, 4, 6-trimethoxyphenyl)phosphine catalyzes the addition reaction of thioesters to norbornenes, giving trans -2-acyl -3-organothionorbornanes. The trans -adducts are predominantly obtained with the acyl group at the endo -position and the organothio group at the exo- position. Aroyl and heteroaroyl thioesters as well as alkanoyl thioesters were reacted, including S -(4-tolyl) phenylthioglyoxylate and methyl 2-(4-tolylthio)-2-oxo-acetate. Graphical abstract: